(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: To determine whether postoperative hypocalcemia after total thyroidectomy is more frequent in malignant disease than benign disease. Methods: This is a Cross sectional study. The sample size is 126. All the patients were selected according to the eligibility criteria by purposive sampling. Patients were analyzed for age, gender, thyroid pathology, preoperative serum calcium, postoperative serum calcium. Results: Postoperative hypocalcemia was found in 37 (29.37%) patients. Most patients were female (Male: Female= 1: 4.2). Patients having low preoperative serum calcium had developed more postoperative hypocalcemia (p<0.03). Postoperative hypocalcemia was associated with thyroid pathology (p<0.009) and age (p<0.006), not associated with sex (p<0.907). In multivariate analysis very little association between malignant disease and postoperative hypocalcemia was found (p<0.07). Conclusion: The incidence of postoperative hypocalcemia following total thyroidectomy is 29.4% that is higher than the anticipated but is comparable to other published series. For total thyroidectomy surgeons should be aware of postoperative hypocalcemia but prophylactic calcium and vitamin D supplement is not mandatory in all cases. Bangladesh J Otorhinolaryngol; April 2019; 25(1): 19-27